MORINGA LEAF (Moringa Oleifera L.) ETHANOL EXTRACT CLAY MASK FORMULATION AS ANTI-AGING - Nurussakinah, Nurussakinah; Fhitriana, Suzan; Khairani, Tetty Noverita; Utari, Sri (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Aging is a human physical change caused by age, psychological, and social factors, especially on the face, neck, upper arms and hands. Aging is unavoidable and goes at different speeds, depending on one's genetics, environment and lifestyle. Synthetic antiocxidant products are many circulated in the market which have a negative impact on health. However Antioxidant compound are widely spread in nature expecially in plant. Moringa leaf is one of plants that contain abundant antioxidant, alkaloids, flavonoids, phenolics, triterpenoids/steroids and tannins. Many of people Switch to natural products. Mask from natural products are not causing irritation or less side effects. clay face mask are mostly used because of their skin rejuvenating abilities. Purpose: To know either Moringa leaf ethanol extract can be formulated in clay mask preparations and the optimal effect is to prevent aging or not. Methods: the research is including how to make clay mask with ethanol extract of Moringa leaves at concentrations of 6%, 8% and 10%. The evaluation of the physical quality of the preparation, testing the effectiveness of clay masks with ethanol extract of Moringa leaves as anti-aging. Result: the preparation is qualify the characteristic test, had a pH of 4.9-5.2, a drying time of 15-23.5 minutes, an o/w emulsion type, was stable for 12 weeks of storage, and was not caused irritation. The best result of anti-aging effectiveness test was at a concentration of 10% with 36.25 moisture content, 23.25 fineness content, 33.75 pores, 20.5 blemishes and 15.5 wrinkles. Conclusion: Moringa leaf ethanol extract can be formulated in clay mask , and is able to give the best anti-aging effect at 10% formula.